Fazer ciência, fazer história: a sociologia da mudança social de Florestan Fernandes e de Costa Pinto - Souza, Patrícia Olsen de [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
This thesis discuss theoretical and interpretative approaches of Florestan Fernandes and L. A. Costa Pinto about social change in Brazil. These two sociologists actively participated in the intellectual debate about the development that happened in the 1950's and 1960's, decisive moment for the implantation of Brazil's capitalism, marked by project contests about the country's routes amid the rising linkage of civil society. In that context, distancing from the hegemonic nationalism in intellectual debate e from separate perspectives - close at a certain point, distant at others - Fernandes and Costa Pinto thought about the singularities of social change in underdeveloped countries, joining the debate of epistemological questions about the apropriate procedures that would allow sociology to contribute with the social change process on course, because these two authors understand the sociological knowledge simultaneously as History products and History producers. Fernandes' main problem was the process and the structural hurdles for the constitution of Brazil's civilization standard - based on democracy, on rationality and on the use of scientific knowledge for social planning. To face these questions, the author distilled a theoretical methodological and conceptual understructure from the sociological synthesis (in Mannheim's sense) of elements extracted from Durkheim,Marx and Weber tradition and, also, from the dialogue with North American sociology. By means of this procedure he identified the cultural delay as the main obstacle for the progress of class society in Brazil - in the 1950's. Amid Brazilian society's radicalisation in the early 1960's, the deepening of intellectual process about development, Fernandes was able to understand Brazil's social change standard as exclusivist, unilateral, formalist, irrational and antidemocratic because it is conducted by elites with limited mental horizons. Costa Pinto analysed social...

Esta Tese discute as abordagens teóricas e interpretativas de Florestan Fernandes e L. A. Costa Pinto sobre a mudança social no Brasil. Os dois sociólogos participaram ativamente do debate intelectual sobre o desenvolvimento travado nas décadas de 1950 e 1960, momento decisivo para a implantação do capitalismo no Brasil, marcado pela disputa de projetos sobre os rumos do país em meio à crescente articulação da sociedade civil. Nesse contexto, distanciando-se do nacionalismo hegemônico no debate intelectual e a partir de perspectivas distintas - próximas em alguns pontos, distantes em outros - Fernandes e Costa Pinto pensaram a particularidade da mudança social nos países subdesenvolvidos, enveredando-se no debate de questões epistemológicas sobre os procedimentos adequados para a sociologia contribuir com o processo de mudança social em curso, pois, para os dois autores, o conhecimento sociológico, além de produto, era visto também como coprodutor da história. O problema central de Fernandes era o processo e os obstáculos estruturais à constituição do padrão de civilização ocidental no Brasil - baseado na democracia, na racionalidade e no uso do conhecimento científico para o planejamento social. Para enfrentar essas questões o autor cunhou um arcabouço teórico-metodológico e conceitual a partir da síntese sociológica (no sentido mannheimiano) de elementos extraídos da tradição durkheimiana, marxista e weberiana e, também, do diálogo com a sociologia norte-americana. Por meio desse procedimento identificou a demora cultural como o principal obstáculo ao avanço da sociedade de classes no Brasil - na década de 1950. Em meio à radicalização da sociedade brasileira no início dos anos de 1960, ao aprofundamento do processo e do debate intelectual sobre o desenvolvimento, Fernandes passou a compreender o padrão de mudança social no Brasil como exclusivista, unilateral, formalista, irracional e...
Keywords: Fernandes, Florestan 1920-1995; Pinto, Luiz de Aguiar Costa 1920-2002; Sociologia; Mudança social; Social change